1993
DOI: 10.1002/gps.930080409
|View full text |Cite
|
Sign up to set email alerts
|

Stress on relative caregivers of dementia sufferers, and predictors of the breakdown of community care

Abstract: SUMMARYThe stress upon the principal relative caregivers of a series of dementia sufferers attending an assessment day hospital was studied. The main variables influencing stress levels were the caregiver's own health self-rating and a measure of behaviour and mood disturbance in the patient. Predictors of the breakdown of community care over a 1-year follow-up period were studied. At 12 months caregiver's 'caseness' on the GHQ was a highly significant predictor. Clinical work with dementia sufferers in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Informal carers (along with formal home care) are then eectively the last bastion between the person with dementia and costly residential care. The experience of these carers is therefore an important area for research, since such research might indicate ways of strengthening their ability to continue in that role (Jerrom et al, 1993).…”
Section: Policy Considerationsmentioning
confidence: 99%
“…Informal carers (along with formal home care) are then eectively the last bastion between the person with dementia and costly residential care. The experience of these carers is therefore an important area for research, since such research might indicate ways of strengthening their ability to continue in that role (Jerrom et al, 1993).…”
Section: Policy Considerationsmentioning
confidence: 99%
“…Studies on dementia have reported of 40% and above institutionalizations within a year. 27 " 29 ' 41 In this study 19% of the patients were institutionalized within two years of the interview. This discrepancy is not surprising, since our study group comprised patients with multiple diagnoses as opposed to only patients with dementia for whom home care may be more difficult to continue.…”
mentioning
confidence: 99%
“…Caregiver burden is one of the most influential factors related to managing dementia patients. Excessive psychological, social, and economic burdens on caregivers can cause social problems such as elder abuse and can also lead to dementia patients being inappropriately institutionalized [8][9][10] , thus elevating the social costs of dementia [11] . Most studies on caregiver burden have been conducted in Western countries, and few studies on the correlates of caregiver burden have been performed in Korea.…”
mentioning
confidence: 99%